Dynamics of Bactrocera dorsalis Resistance to Seven Insecticides in South China - Xinlian Li; Peizheng Li; Doudou Li; Xinyan Cai; Shiwei Gu; Ling Zeng; Daifeng Cheng; Yongyue Lu (Insects, 2024)
Bactrocera dorsalis is a highly invasive and destructive pest distributed worldwide. Chemical insecticides remain the primary measure for their control; however, this species has already developed resistance to several insecticides. In recent years, there have been several reports of monitoring B. dorsalis resistance in China, but continuous monitoring results are lacking and do not even span a decade. In this study, we monitored the dynamics of resistance to seven insecticides among 11 geographically distinct Chinese populations of B. dorsalis (2010–2013; follow-up in 2023). The 11 populations were found to adapt rapidly to antibiotic insecticides (spinosad, emamectin benzoate, and avermectin), reaching high levels of insecticide resistance in several areas. Overall, a decreasing trend in resistance to organophosphorus insecticides (chlorpyrifos and trichlorfon) was observed, whereas pyrethroid (beta-cypermethrin and cyhalothrin) resistance trends were observed to both increase and decrease. The monitoring of field resistance among different B. dorsalis populations over the duration of this study is important for improving the efficiency and sustainability of agricultural pest management, and the results provide a scientific basis for the development of more effective resistance management strategies.